Is the Neoproterozoic oxygen burst a supercontinent legacy? - Macouin, Melina; Roques, Damien; Rousse, Sonia; Ganne, Jerome; Denele, Yoann; Trindade, Ricardo Y. (Frontiers in Earth Science, 2015)
The Neoproterozoic (1000–542 Myr ago) witnessed the dawn of Earth as we know it with modern-style plate tectonics, high levels of O2 in atmosphere and oceans and a thriving fauna. Yet, the processes leading to the fully oxygenation of the external envelopes, its exact timing and its link with the inner workings of the planet remain poorly understood. In some ways, it is a "chicken and egg" question: did the Neoproterozoic Oxygenation Event (NOE) cause life blooming, low-latitudes glaciations and perturbations in geochemical cycles or is it a consequence of these phenomena? Here, we suggest that the NOE may have been triggered by multi-million years oxic volcanic emissions along a protracted period at the end of the Neoproterozoic when continents were assembled in the Rodinia supercontinent. We report a very oxidized magma source at the upper mantle beneath a ring of subducting margins around Rodinia, and detail here the evidence at the margin of the Arabian shield. We investigate the 780 Ma Biotite and Pink granites and associated rocks of the Socotra Island with rock magnetic and petrographic methods. Magnetic susceptibility and isothermal remanent magnetization acquisitions show that, in these granites, both magnetite and hematite are present. Hematite subdivides magnetite grains into small grains. Magnetite and hematite are found to be primary, and formed at the early magmatic evolution of the granite at very high oxygen fugacity. Massive degassing of these oxidized magmas would reduce the sink for oxygen, and consequently contribute to its rise in the atmosphere with a net O2 flux of at least 2.25 x 107 Tmol. Our conceptual model provides a deep Earth link to the NOE and implies the oxygenation burst has occurred earlier than previously envisaged, paving the way for later changes in the outer envelopes of the planet epitomized on the extreme Neoproterozoic glaciations and the appearance of the first animals.